2017
DOI: 10.1016/j.eurpsy.2017.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Confirmatory Factor Analysis of the Postpartum Depression Screening Scale-21 in a Sample of Portuguese Women

Abstract: IntroductionThe postpartum depression screening scale (PDSS; Beck & Gable, 2002) is a widely used measure to assess women's depressive symptoms after their children's birth. Pereira et al. adapted, validated and developed a short-version of PDSS for Portuguese women (PDSS-21).ObjectiveTo examine the factor structure of the PDSS–21, using confirmatory factor analysis (CFA) in a sample of Portuguese women in the postpartum period.MethodsThe sample was composed of 208 women (mean age = 32.72; SD = 4.49) who c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…However, many studies have confirmed that this value is satisfactory (e.g. Bukhari et al, 2020;Marques et al, 2017). Particularly, χ 2 (366) 5 1090.136; CMIN/DF 5 2.979 < 5; p < 0.01; GFI 5 0.889 > 0.8; CFI 5 0.938 > 0.9; TLI 5 0.921 > 0.9; and RMSEA 5 0.057 < 0.8 (Anderson and Gerbing, 1988;Hu and Bentler, 1999).…”
Section: The Reliability and Validity Of Variablesmentioning
confidence: 90%
“…However, many studies have confirmed that this value is satisfactory (e.g. Bukhari et al, 2020;Marques et al, 2017). Particularly, χ 2 (366) 5 1090.136; CMIN/DF 5 2.979 < 5; p < 0.01; GFI 5 0.889 > 0.8; CFI 5 0.938 > 0.9; TLI 5 0.921 > 0.9; and RMSEA 5 0.057 < 0.8 (Anderson and Gerbing, 1988;Hu and Bentler, 1999).…”
Section: The Reliability and Validity Of Variablesmentioning
confidence: 90%
“…Participants were asked to fill in a booklet, including sociodemographic questions, the Portuguese preliminary version of the POCS [ 17 ], the Perinatal Anxiety Screening Scale (PASS) [ 30 , 31 ] and the Postpartum Depression Screening Scale [ 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…All participants were interviewed with the Diagnostic Interview for Psychological Distress—Postpartum [ 33 ], a brief semi-structured diagnostic interview developed based upon the DSM-5 [ 16 ] criteria for the most prevalent perinatal psychiatric disorders, including the Obsessive–Compulsive Disorder.…”
Section: Methodsmentioning
confidence: 99%